2022
DOI: 10.3389/fneur.2022.968111
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Mind in migraine and medication-overuse headache: A cross-sectional study

Abstract: BackgroundTheory of Mind (ToM) is the ability to predict and anticipate others' behaviors through the mental state attribution process. This study aims to investigate the ToM in patients with medication-overuse headache (MOH) and episodic migraine (EM) and to compare it with healthy controls (HC).MethodsThis study enrolled patients with MOH, patients with EM, and HC. ToM was assessed through the Theory of Mind Assessment Scale (ThOMAS), which includes four subscales: Scale A, I-Me, Scale B, Other-Self, Scale C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 38 publications
(29 reference statements)
2
9
0
Order By: Relevance
“…A 2022 study provides perhaps more insight by suggesting that patients with MOH, compared with patients with episodic migraine and healthy controls, exhibited higher levels of alexithymia, a reduced capacity for introspection leading to an inability to recognize and express feelings and emotions 19 . This is described as causing confusion in distinguishing between emotions and bodily sensations and, in the setting of headache, could contribute to poor coping skills and facilitate medication overuse.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2022 study provides perhaps more insight by suggesting that patients with MOH, compared with patients with episodic migraine and healthy controls, exhibited higher levels of alexithymia, a reduced capacity for introspection leading to an inability to recognize and express feelings and emotions 19 . This is described as causing confusion in distinguishing between emotions and bodily sensations and, in the setting of headache, could contribute to poor coping skills and facilitate medication overuse.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…18 A 2022 study provides perhaps more insight by suggesting that patients with MOH, compared with patients with episodic migraine and healthy controls, exhibited higher levels of alexithymia, a reduced capacity for introspection leading to an inability to recognize and express feelings and emotions. 19 This is described as causing confusion in distinguishing between emotions and bodily sensations and, in the setting of headache, could contribute to poor coping skills and facilitate medication overuse. Early recognition of such difficulties by the provider could aid management, for example by leading to the alteration of treatment recommendations (eg, earlier use of calcitonin gene-related peptide [CGRP] medications that are not as associated with MOH), enhanced patient education of the risks of MOH, stricter monitoring of medication use and earlier follow-up, and heightened provider awareness.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…When referring to psychosocial vulnerabilities, it is important to include also all those activity limitations and social-interactions restrictions being impacted by chronic pain [21]. Recent evidence showed an association between migraine and social cognitive functioning [22][23][24], whose decline could be responsible for dysfunctional social behaviors and personal distress. The term "social cognition" is a wide construct that refers to all mental operations that allow to decipher information about the intentions and affective states of social partners [25].…”
Section: Introductionmentioning
confidence: 99%
“…Raimo [24] explored the neuropsychological correlates of ToM and found that CM patients had evident di culties in the cognitive dimension involved in inferring other's mental states. Romozzi [23] compared CM + MO, EM, and HC in complex emotion recognition, knowledge about one's own and other person's mental states, and alexithymic levels and found an impairment in all considered dimensions in CM + MO patients. Therefore, it appears that a dysfunction in social cognitive abilities may represent a critical characteristic of CM/CM + MO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation